A flame retardant silicone rubber foam composite material and preparation method thereof
By adding metal organic frame materials and modified Elostone nanotubes to silicone rubber foam composite materials, the problem that existing materials cannot meet the flame retardant requirements in the high-tech field is solved, and the efficient flame retardant and mechanical properties of the materials are improved. .
Patent Information
- Application Number
- CN202410108919.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-01-26
AI Technical Summary
The existing silicone rubber foam materials cannot meet the flame retardant requirements in high-tech applications such as battery modules and aviation filling, and the amount of flame retardant added affects the mechanical properties of the material.
The flame retardancy and mechanical properties of the material are synergistically improved by adding metal organic frame material and modified Elosite nanotubes to the silicone rubber foam composite. Metal organic frame materials adsorb and dilute combustible gas during combustion to promote catalytic carbon formation, while modified Elosite nanotubes enhance flame retardant capacity by cooling and enhancing the strength of the carbon layer.
The flame retardant and mechanical properties of composite materials are significantly improved, and the minimal addition of organic frame materials can significantly improve the material's ultimate oxygen index and combustion grade.
Smart Images

Figure CN118006127B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and in particular to a flame-retardant silicone rubber foam composite material and a preparation method thereof. Background Art
[0002] The main chain of silicone rubber foam material is composed of inorganic structure Si-O-Si chain links. It has excellent properties such as non-flammability, high temperature resistance, electrical insulation, oxidation resistance, weather resistance, corrosion resistance, and low-pressure permanent compression set. It can be used as a high-performance material for sealing, damping, heat insulation, waterproofing, moisture-proofing, and inert filling. It is widely used in aerospace, new energy vehicles, wires and cables, building materials and other fields. However, silicone rubber foam that has not been flame retardant treated still cannot meet the application conditions of high-tech fields such as battery modules and aviation fillings. Therefore, it is of great significance to develop a flame retardant silicone rubber foam composite material with a small amount of flame retardant additives and excellent flame retardant properties.
[0003] The silicone rubber foam on the market mainly uses aluminum hydroxide, ammonium polyphosphate and other flame retardants, which not only require a large amount of addition but also seriously affect the mechanical properties of the material. Summary of the Invention
[0004] In order to overcome the deficiencies of the prior art, the present invention provides a flame-retardant silicone rubber foam composite material, which synergistically improves the flame retardancy and mechanical properties of the silicone rubber foam composite material by metal-organic framework materials and modified halloysite nanotubes.
[0005] A flame-retardant silicone rubber foam composite material. The raw materials of the composite material comprise, in parts by weight, 150 parts of a finished base rubber, 155 parts of hydroxy silicone oil, 2-4 parts of a platinum catalyst, 1 part of an inhibitor, 2-20 parts of a metal-organic framework material, 2-20 parts of modified halloysite nanotubes, and 20-25 parts of hydrogenated silicone oil.
[0006] Metal-organic framework material is a hybrid material formed by self-assembly of inorganic metal salts and organic ligands through coordination bonds. It has a molecular-level framework structure. The metal-organic framework material adsorbs and dilutes combustible gases during combustion and can promote catalytic carbonization. The metal oxides after pyrolysis adhere to the material collectively, isolating the infiltration of oxygen and slowing down further combustion of the material; the release of water between the halloysite nanotube layers has a cooling effect, and silica can synergistically stabilize the carbon layer. The modified halloysite nanotubes improve the strength of the carbon layer, making the residual carbon in the composite material denser, and enhancing the formation of a dense residual carbon layer, thereby enhancing the flame retardant ability of the metal framework organic material and the modified halloysite nanotubes; the inhibitor ensures the cross-linking polymerization speed of the silicone rubber foam. When the inhibitor is added in too little amount, the effect of delaying polymerization will be weakened, and the material will easily cross-link rapidly; when the inhibitor is added in too much amount, the silicone rubber foam will be difficult to cross-link and mold.
[0007] The metal elements of the metal-organic framework material can catalyze carbonization during the combustion process. In addition to the rapid catalytic carbonization of its own organic ligands during pyrolysis, the carbonization is also accelerated by the modified halloysite nanotubes. The modified halloysite nanotubes are green and environmentally friendly, and have good compatibility with the silicone rubber foam material matrix. The tubular crystal structure effectively improves the tensile strength and elongation at break of the silicone rubber foam, thereby improving the mechanical properties of the composite material. When the composite material is heated and burned, the metal-organic framework material and the modified halloysite nanotubes synergistically flame retardant and smoke suppressant. The dense carbon layer formed on the surface of the composite material effectively blocks heat and oxygen from entering the material matrix, preventing further combustion of the composite material. A very small amount of added organic framework material can significantly improve the limiting oxygen index and combustion level of the material.
[0008] Optionally, the modified halloysite nanotubes are halloysite nanotubes modified with bio-based materials.
[0009] Optionally, the bio-based material is selected from any one of chitosan, cyclodextrin, starch, and phytic acid.
[0010] Optionally, the metal-organic framework material is selected from one of a cobalt-based metal-organic framework, an aluminum-based metal-organic framework, an iron-based metal-organic framework and a zinc-based metal-organic framework.
[0011] Optionally, the mass ratio of the metal organic framework material to the modified halloysite nanotubes is 1:1-5.
[0012] When the amount of modified halloysite nanotubes added is too small, the thickness of the carbon layer and the residual carbon rate of the composite material during thermal combustion are both low. When the amount of modified halloysite nanotubes added is too large, the flame retardant efficiency of the composite material is high and the mechanical properties of the composite material are affected.
[0013] Optionally, the inhibitor is composed of the following raw materials in the following mass ratios:
[0014] 95-99 wt% of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 20-30 mPa·s;
[0015] 2-Methyl-3-butyn-2-ol 1-5 wt%.
[0016] When the content of 2-methyl-3-butyn-2-ol is too high, the foaming reaction cannot proceed. When the content of 2-methyl-3-butyn-2-ol is too low, the foaming reaction speed is too fast, and the raw materials in the composite material are not mixed evenly, which affects the flame retardant and mechanical properties of the composite material.
[0017] Optionally, the finished rubber base is composed of the following raw materials in the following mass ratios:
[0018] 70-90 wt% of vinyl-terminated disiloxane;
[0019] Fumed silica 10-30wt%;
[0020] The hydroxy silicone oil is composed of the following raw materials in parts by weight:
[0021] 120-150 parts of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 1500 mPa·s;
[0022] and 5-35 parts of α,ω-dihydroxypolydimethylsiloxane having a viscosity of 20-30 mPa·s;
[0023] Another aspect of the present invention provides a method for preparing the flame retardant silicone rubber foam composite material, comprising the following steps:
[0024] S1. Evenly mix the finished base rubber, hydroxy silicone oil, platinum catalyst, and inhibitor in proportion to obtain a second mixture;
[0025] S2. adding the metal organic framework material and the modified halloysite nanotubes to the second mixture in proportion, and mixing them uniformly to obtain a third mixture;
[0026] S3, adding hydrogen-containing silicone oil to the third mixture, and mixing uniformly to obtain a fourth mixture;
[0027] S4. Pour the fourth mixture into a mold and foam it to obtain a flame retardant rubber foam composite material.
[0028] Optionally, the foaming operation is specifically as follows: first foaming at room temperature, and then heating and foaming.
[0029] Optionally, the temperature of the room temperature foaming is 10-30° C., and the time of the room temperature foaming is 5-60 min; the temperature of the heated foaming is 80-150° C., and the time of the heated foaming is 5-15 min.
[0030] The beneficial effects of the present invention are: the modified halloysite nanotubes are green and environmentally friendly, have good compatibility with the silicone rubber foam material matrix, and the tubular crystal structure effectively improves the tensile strength and elongation at break of the silicone rubber foam, thereby improving the mechanical properties of the composite material; when the composite material is heated and burned, the metal organic framework material and the modified halloysite nanotubes synergistically flame retardant and smoke suppressant, and the dense carbon layer formed on the surface of the composite material effectively blocks heat and oxygen from entering the material matrix, preventing further combustion of the composite material. A very small amount of added organic framework material can significantly improve the limiting oxygen index and combustion level of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the carbon residue of the flame-retardant silicone rubber foam composite material of Example 6 of the present invention.
[0032] Figure 2 This is a scanning electron microscope image of the carbon residue of the XC800-H foamed silica gel material in comparative example 1 of the present invention. DETAILED DESCRIPTION
[0033] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0034] The raw material information involved in the present invention is shown in Table 1.
[0035] Table 1 Raw material information
[0036]
[0037]
[0038] The preparation method of the modified halloysite nanotubes and metal organic framework materials of the present invention is as follows:
[0039] The preparation method of chitosan-modified halloysite nanotubes comprises the following steps:
[0040] 1) adding 1.7-5.1 g of chitosan to a 2 wt % acetic acid solution and stirring uniformly to obtain a first mixture;
[0041] 2) adding 5-15 g of halloysite nanotubes to the first mixture, stirring in a constant temperature water bath at 80° C. for 12 h, filtering, washing, and drying to obtain chitosan-modified halloysite nanotubes.
[0042] The preparation method of phytic acid-modified halloysite nanotubes comprises the following steps:
[0043] 1) 50-200 g of halloysite nanotubes were added to 500 ml of anhydrous ethanol and dispersed uniformly. 5-10 g of an aminosilane coupling agent (KH550) was then added and stirred in a 70° C. constant temperature water bath for 12 h. The precipitate was filtered, washed, and dried to obtain amino-modified halloysite nanotubes.
[0044] 2) 5-20 g of amino-modified halloysite nanotubes were dispersed in 400 ml of pure water, and 4.95-19.8 g of phytic acid solution was added. The mixture was stirred in a constant temperature water bath at 80° C. for 12 h. After filtering, washing, and drying, phytic acid-modified halloysite nanotubes were obtained.
[0045] The preparation method of aluminum-based metal organic framework material comprises the following steps:
[0046] 1) Add 11.25-22.5 g of aluminum salt and 4.98-9.96 g of terephthalic acid to a beaker containing 150 ml of deionized water. Place the beaker on an ultrasonic dissolution table for 30 minutes to form an emulsion.
[0047] 2) The emulsion was poured into a 500 ml polytetrafluoroethylene-lined autoclave and reacted in a 180° C. forced air drying oven for 72 h. The emulsion after the reaction was placed in a centrifuge at 3000 r / min for 10 min to precipitate. The precipitate was washed three times with deionized water and dried in a 150° C. drying oven for 4 h to obtain an aluminum-based metal-organic framework.
[0048] The preparation method of the cobalt-based metal organic framework material comprises the following steps:
[0049] 1) dissolving 2-3 g of cobalt salt and 4-5 g of 2-methylimidazole in 200 ml of methanol and stirring at room temperature for 24 h to obtain a first mixture;
[0050] 2) centrifuging the first mixture to obtain a precipitate, washing the precipitate three times with methanol, and then drying the precipitate to obtain a cobalt-based metal-organic framework material.
[0051] Example
[0052] Example 1
[0053] A flame retardant silicone rubber foam composite material is prepared by the following steps:
[0054] S1, 105g of viscosity 4×10 5 ~6×10 5 mPa·s vinyl-terminated disiloxane and 45 g of fumed silica were mixed evenly, and then 120 g of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 1500 mPa·s, 35 g of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 20-30 mPa·s, 2 g of 3000 ppm platinum catalyst, and 0.95 g of 20-30 mPa·s α,ω-dihydroxypolydimethylsiloxane and 0.05 g of 2-methyl-3-butyn-2-ol were added and stirred evenly to obtain a second mixture;
[0055] S2, adding 2 g of aluminum metal organic framework material and 2 g of chitosan modified halloysite nanotubes to the second mixture, stirring evenly to obtain a third mixture;
[0056] S3, adding 20 g of hydrogenated silicone oil to the third mixture, and mixing uniformly to obtain a fourth mixture;
[0057] S4, quickly pouring the fourth mixture into a mold, foaming at 10° C. for 60 min, and then placing the mold in a blast drying oven at 80° C. for further cross-linking and foaming for 15 min to obtain a flame retardant rubber foam composite material;
[0058] The preparation method of chitosan-modified halloysite nanotubes comprises the following steps:
[0059] 1) adding 3.4 g of chitosan to 500 ml of a 2 wt % acetic acid solution and stirring uniformly to obtain a first mixture;
[0060] 2) adding 10 g of halloysite nanotubes to the first mixture, stirring in a constant temperature water bath at 80° C. for 12 h, filtering using a vacuum filter to obtain a precipitate, washing the precipitate three times with pure water, and drying in a drying oven at 80° C. for 24 h to obtain chitosan-modified halloysite nanotubes;
[0061] The preparation method of aluminum-based metal organic framework material comprises the following steps:
[0062] 1) Add 11.25 g of aluminum nitrate nonahydrate and 4.98 g of terephthalic acid to a beaker containing 150 ml of deionized water. Place the beaker on an ultrasonic dissolution table for 30 minutes to form an emulsion.
[0063] 2) The emulsion was poured into a 500 ml polytetrafluoroethylene-lined autoclave and reacted in a 180° C. forced air drying oven for 72 h. The emulsion after the reaction was placed in a centrifuge at 3000 r / min for 10 min to precipitate. The precipitate was washed three times with deionized water and then dried in a 150° C. drying oven for 4 h to obtain an aluminum-based metal-organic framework.
[0064] Example 2
[0065] A flame retardant silicone rubber foam composite material, which is different from Example 1 in that it is prepared by the following steps:
[0066] S1, 135g of viscosity 4×10 5 ~6×10 5 mPa·s vinyl-terminated disiloxane and 15 g of fumed silica were mixed evenly, and then 150 g of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 1500 mPa·s, 5 g of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 20-30 mPa·s, 4 g of 3000 ppm platinum catalyst, and a mixture of 0.99 g of 20-30 mPa·s α,ω-dihydroxypolydimethylsiloxane and 0.01 g of 2-methyl-3-butyn-2-ol were added and stirred evenly to obtain a second mixture;
[0067] S2, adding 20 g of aluminum metal organic framework material and 20 g of chitosan modified halloysite nanotubes to the second mixture, stirring evenly to obtain a third mixture;
[0068] S3, adding 25 g of hydrogenated silicone oil to the third mixture, and mixing uniformly to obtain a fourth mixture;
[0069] S4. Pour the fourth mixture into a mold quickly, foam it at 30° C. for 5 minutes, and then place the mold in a forced air drying oven at 150° C. for further cross-linking and foaming for 5 minutes to obtain a flame-retardant rubber foam composite material.
[0070] Example 3
[0071] A flame retardant silicone rubber foam composite material, which is different from Example 1 in that it is prepared by the following steps:
[0072] S1, 120g of viscosity 4×10 5 ~6×10 5 mPa·s vinyl-terminated disiloxane and 30 g of fumed silica were mixed evenly, and then 135 g of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 1500 mPa·s, 20 g of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 20-30 mPa·s, 3 g of 3000 ppm platinum catalyst, and 0.97 g of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 20-30 mPa·s and 0.03 g of 2-methyl-3-butyn-2-ol were added and stirred evenly to obtain a second mixture;
[0073] S2, adding 10 g of aluminum metal organic framework material and 15 g of chitosan modified halloysite nanotubes to the second mixture, stirring evenly to obtain a third mixture;
[0074] S3, adding 23 g of hydrogenated silicone oil to the third mixture, and mixing uniformly to obtain a fourth mixture;
[0075] S4. Pour the fourth mixture into a mold quickly, foam it at 30° C. for 5 minutes, and then place the mold in a forced air drying oven at 150° C. for further cross-linking and foaming for 5 minutes to obtain a flame-retardant rubber foam composite material.
[0076] Example 4
[0077] A flame retardant silicone rubber foam composite material, which is different from Example 1 in that it is prepared by the following steps:
[0078] S1, 115g of viscosity 4×10 5 ~6×10 5mPa·s vinyl-terminated disiloxane and 35 g of fumed silica were mixed evenly, and then 150 g of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 1500 mPa·s, 5 g of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 20-30 mPa·s, 4 g of 3000 ppm platinum catalyst, and a mixture of 0.98 g of 20-30 mPa·s α,ω-dihydroxypolydimethylsiloxane and 0.02 g of 2-methyl-3-butyn-2-ol were added and stirred evenly to obtain a second mixture;
[0079] S2, adding 5 g of aluminum metal organic framework material and 15 g of chitosan modified halloysite nanotubes to the second mixture, stirring evenly to obtain a third mixture;
[0080] S3, adding 23 g of hydrogenated silicone oil to the third mixture, and mixing uniformly to obtain a fourth mixture;
[0081] S4. Pour the fourth mixture into a mold quickly, foam it at 30° C. for 5 minutes, and then place the mold in a forced air drying oven at 80° C. for further cross-linking and foaming for 10 minutes to obtain a flame-retardant rubber foam composite material.
[0082] Example 5
[0083] A flame-retardant silicone rubber foam composite material is different from Example 4 in that the modified halloysite nanotubes are phytic acid-modified halloysite nanotubes.
[0084] The preparation method of phytic acid-modified halloysite nanotubes comprises the following steps:
[0085] 1) 200 g of halloysite nanotubes were added to 500 ml of anhydrous ethanol and dispersed uniformly. 5 g of aminosilane coupling agent (KH550) was then added and stirred in a constant temperature water bath at 70° C. for 12 h. The precipitate was filtered, washed, and dried to obtain amino-modified halloysite nanotubes.
[0086] 2) The amino-modified modified halloysite nanotubes were dispersed in 400 ml of pure water, 19.8 g of phytic acid solution was added, and the mixture was stirred in a constant temperature water bath at 80° C. for 12 h. The precipitate was filtered using a vacuum filter, and the precipitate was washed three times with pure water and dried in a drying oven at 80° C. for 24 h to obtain phytic acid-modified modified halloysite nanotubes.
[0087] Example 6
[0088] A flame-retardant silicone rubber foam composite material, which is different from Example 4 in that the metal organic framework material is a cobalt-based metal organic framework material.
[0089] The preparation method of the cobalt-based metal organic framework material comprises the following steps:
[0090] 1) dissolving 2.33 g of cobalt nitrate hexahydrate and 4.93 g of 2-methylimidazole in 200 ml of methanol and stirring at room temperature for 24 h to obtain a first mixture;
[0091] 2) The first mixture was centrifuged to obtain a precipitate, the precipitate was washed three times with methanol, and then dried at 80° C. to obtain a cobalt-based metal-organic framework material.
[0092] Example 7
[0093] A flame-retardant silicone rubber foam composite material is different from Example 4 in that the added amount of phytic acid-modified halloysite nanotubes is 10 g.
[0094] Example 8
[0095] A flame-retardant silicone rubber foam composite material is different from Example 4 in that the added amount of phytic acid-modified halloysite nanotubes is 25 g.
[0096] Example 9
[0097] A flame-retardant silicone rubber foam composite material is different from Example 4 in that the added amount of phytic acid-modified halloysite nanotubes is 5 g.
[0098] Example 10
[0099] A flame-retardant silicone rubber foam composite material is different from Example 4 in that the added amount of phytic acid-modified halloysite nanotubes is 50 g.
[0100] Comparative Example
[0101] Comparative Example 1
[0102] A commercially available flame retardant silicone rubber foam is XC800-H type foamed silicone rubber.
[0103] Comparative Example 2
[0104] A flame-retardant silicone rubber foam composite material is different from Example 4 in that: S2, 5g of cobalt metal organic framework material and 10g of halloysite nanotubes are added to the second mixture, and stirred evenly to obtain a third mixture.
[0105] Comparative Example 3
[0106] A flame-retardant silicone rubber foam composite material is different from Example 4 in that: S2, 5g of cobalt metal organic framework material and 15g of halloysite nanotubes are added to the second mixture, and stirred evenly to obtain a third mixture.
[0107] Comparative Example 4
[0108] A flame-retardant silicone rubber foam composite material is different from Example 4 in that: S2, 5g of cobalt metal organic framework material and 20g of halloysite nanotubes are added to the second mixture, and stirred evenly to obtain a third mixture.
[0109] The preparation methods of the flame-retardant silicone rubber foam composite materials of Examples 2-10 and Comparative Examples 1-4 are the same as that of Example 1.
[0110] Performance testing
[0111] The following performance tests were performed on the flame-retardant silicone rubber foam composite materials provided in Examples 1-10 and Comparative Examples 1-4 of the present invention:
[0112] Limiting oxygen index: The flame retardant silicone rubber foam composite materials of Examples 1-10 and Comparative Examples 1-4, each with a size of 130.0 mm × 10.0 mm × 10.0 mm, were respectively measured for limiting oxygen index according to GB / T 2406.1-2008.
[0113] Flame retardant grade: flame retardant silicone rubber foam composite materials of Examples 1-10 and Comparative Examples 1-4, each with a size of 127.0 mm × 12.7 mm × 3.0 mm, were tested for flame retardant grade according to ASTM D3801-2010.
[0114] Tensile strength and elongation at break: The tensile strength and elongation at break of the flame retardant silicone rubber foam composite materials of Examples 1-10 and Comparative Examples 1-4 were tested according to GB / T528-2009.
[0115] Three samples were taken for each example and comparative example, and the test results were averaged. The specific test results are shown in Table 2.
[0116] Table 2 Performance results
[0117]
[0118]
[0119] According to Table 2 and Figure 1-2 The performance comparison shows that the microscopic carbon morphology of pure silicone rubber foam after combustion is Figure 1 It can be seen that the carbon layer is severely cracked, and these cracks provide channels for oxygen to enter the material matrix, promoting further combustion of the matrix; and the microscopic residual carbon morphology of the flame-retardant silicone rubber foam composite material prepared by the present invention after combustion shows that the carbon layer is continuous and dense, with almost no cracks. This dense carbon layer can effectively block the entry of oxygen to prevent the continued combustion of the material matrix.
[0120] According to the performance comparison of Examples 1-10 and Comparative Examples 2-4, it can be seen that when the metal organic framework material is a cobalt-based metal organic framework material, the modified halloysite nanotubes are phytic acid-modified halloysite nanotubes, and the mass ratio of the cobalt-based organic framework material to the phytic acid-modified halloysite nanotubes is 1:3, the flame retardant grade and mechanical properties of the flame retardant silicone rubber foam composite material are significantly improved.
[0121] Finally, it should be noted that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or substitute equivalents for some of the technical features. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A flame retardant silicone rubber foam composite material, characterized in that: The raw material composition of the composite material includes, by weight: 150 parts of finished base glue, 155 parts of hydroxy silicone oil, 2-4 parts of platinum catalyst, 1 part of inhibitor, 2-20 parts of metal organic framework material, 2-20 parts of modified halloysite nanotubes and 20-25 parts of hydrogen-containing silicone oil; The modified halloysite nanotubes are halloysite nanotubes modified with bio-based materials; The bio-based material is selected from any one of chitosan, cyclodextrin, starch and phytic acid; The metal organic framework material is selected from one of a cobalt-based metal organic framework, an aluminum-based metal organic framework, an iron-based metal organic framework and a zinc-based metal organic framework.
2. The flame retardant silicone rubber foam composite material according to claim 1, characterized in that: The mass ratio of the metal organic framework material to the modified halloysite nanotube is 1:1-5.
3. The flame retardant silicone rubber foam composite material according to claim 1, characterized in that: The inhibitor is composed of the following raw materials in the following mass ratio: 20-30 mPa·s α,ω-dihydroxy polydimethylsiloxane 95-99 wt%; 2-Methyl-3-butyn-2-ol 1-5wt%.
4. The flame retardant silicone rubber foam composite material according to claim 1, characterized in that: The finished rubber base is composed of the following raw materials in the following mass ratios: 70-90 wt% of vinyl-terminated disiloxane; Fumed silica 10-30wt%; The hydroxy silicone oil is composed of the following raw materials in parts by weight: 120-150 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 1500 mPa·s; and 5-35 parts of α,ω-dihydroxypolydimethylsiloxane having a viscosity of 20-30 mPa·s.
5. A method for preparing a flame retardant silicone rubber foam composite material, for preparing the flame retardant silicone rubber foam composite material as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1. Evenly mix the finished base rubber, hydroxy silicone oil, platinum catalyst and inhibitor according to a certain proportion to obtain a second mixture; S2, adding the metal organic framework material and the modified halloysite nanotube into the second mixture in proportion, mixing them evenly, to obtain a third mixture; S3, adding the hydrogen-containing silicone oil to the third mixture, and mixing them evenly to obtain a fourth mixture; S4, pouring the fourth mixture into a mold and foaming it to obtain a flame retardant rubber foam composite material.
6. The method for preparing a flame retardant silicone rubber foam composite material according to claim 5, characterized in that: The foaming operation is specifically as follows: First, foam at room temperature, then heat and foam.
7. The method for preparing a flame retardant silicone rubber foam composite material according to claim 6, characterized in that: The temperature of the room temperature foaming is 10-30°C, and the time of the room temperature foaming is 5-60 minutes; the temperature of the heated foaming is 80-150°C, and the time of the heated foaming is 5-15 minutes.